Question

Open in App

Updated on : 2022-09-05

Solution

Verified by Toppr

Correct option is C)

for mass $M$,

$Ma=Mg−T....(1)$

for mass $m$,

for mass $m$,

$ma=T−mg.....(2)$

$(1)+(2),a=(M+m)(M−m)g $

now using the formula, $v_{2}−u_{2}=2as$

here, $u=0,s=d$ so , $v_{2}=2ad=(M+m)2(M−m)gd $

$∴v=(M+m)2(M−m)gd $

Ans:(C)

$(1)+(2),a=(M+m)(M−m)g $

now using the formula, $v_{2}−u_{2}=2as$

here, $u=0,s=d$ so , $v_{2}=2ad=(M+m)2(M−m)gd $

$∴v=(M+m)2(M−m)gd $

Ans:(C)

Solve any question of Work, Energy and Power with:-

Was this answer helpful?

0

0